Modulations of event-related potentials by tactile negative priming - Wesslein, A; Naumann, E; Spence, C; Frings, C (Lippincott, Williams and Wilkins, 2019)
Negative priming (NP) refers to the finding that responses to previously irrelevant stimuli are impeded relative to responses to new stimuli. To date, NP has been demonstrated in the visual, auditory, and tactile sensory modalities with both inhibitory processes and retrieval-based processes contributing to the effect. To gain deeper insights into the role of both processes, event-related potentials (ERPs) have been measured during NP tasks with visual and separately with auditory stimuli. The specific patterns of ERP correlates are mixed, yet it can generally be concluded from previous research that amplitudes of both the N2 and the P3 reflect important components of NP. We present the first study to assess the ERP correlates of NP in the tactile modality. We observe a significant modulation of the P3 but not of the N2, thus providing tentative support for the existence of modality-specific differences in the ERP correlates of NP.